(untitled) (Fiep Bulletin - online, 2011)
The Mobile Urgency Care Service (Serviço de Atendimento Móvel de Urgência – SAMU) works 24 hours a day aiming to improve the quality of assistance to trauma victims and specialized care offered to people affected by clinical emergencies in general, providing fast and early care in the event’s location. Given this scenery involving mobile pre-hospital care, this study aims to identify the shift with the most procedures performed by SAME/Natal; to characterize clinical and trauma injuries according to type, frequency and gender. It’s a descriptive type study, with quantitative approach and retrospective data collected from the SAMU/Natal, RN database. The population of the study was constituted of 16,185 procedures performed from February 2007 to February 2008. The work was approved by the record protocol in the Comitê de Ética e Pesquisa from Hospital Universitário Onofre Lopes, protocolo n°. 153/07. The results show that the care procedures were predominant in the daytime period, Sunday was the day with the most procedures, and most procedures were clinical. Regarding clinical procedures, those of metabolic nature were predominant. As for trauma procedures, collisions provoked by traffic accidents were predominant.